Where you go depends on where you come from: The influence of father's employment status on young adult's labour market experiences - Wouter Zwysen (University of Essex, Institute for Social and Economic Research (ISER), 2013)
The transmission of economic (dis-)advantage over time should take into account the probability of employment as well as employment conditions, especially given the recent increase in the proportion of non-working people. We study the effect of young people experiencing their father not working on a range of labour market outcomes as young adults using the UKHLS. We find that children of non-working fathers are less likely to work themselves and are less satisfied when working despite similar experiences to their peers in terms of wages and contract. Testing several mediators, we find indications that these young adults experience worklessness as a less negative experience.
Keywords: 330; intergenerational transmission; worklessness; family background